2015
DOI: 10.1007/s11882-015-0531-3
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling and Repair in Rhinosinusitis

Abstract: Remodeling refers to the development of specific but potentially irreversible structural changes in tissue. Caucasian eosinophilic chronic rhinosinusitis (CRS) with polyps associated or not with cystic fibrosis was discriminated by edema from CRS without nasal polyps, characterized by extensive fibrotic fields. However, changes in epithelial and extracellular matrix structures are common findings in all types of chronic inflammatory diseases of upper airways, but rarely specific and highly variable in extend. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…As far as we know, there is no prior study demonstrating a relationship between mucosal denervation and remodeling. Tissue remodeling is usually seen as a consequence of inflammatory reaction . It remains unclear whether the tissue remodeling in our study was induced primarily by mucosal denervation or secondarily by chronic inflammation following mucosal denervation.…”
Section: Discussionmentioning
confidence: 72%
“…As far as we know, there is no prior study demonstrating a relationship between mucosal denervation and remodeling. Tissue remodeling is usually seen as a consequence of inflammatory reaction . It remains unclear whether the tissue remodeling in our study was induced primarily by mucosal denervation or secondarily by chronic inflammation following mucosal denervation.…”
Section: Discussionmentioning
confidence: 72%
“…Researchers found a close relationship between inflammation and remodeling [20, 21]. Traditionally, chronic inflammation is believed to be the cause of remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, chronic inflammation is believed to be the cause of remodeling. However, new evidence suggests that remodeling is an active primary process that could occur with ongoing inflammation and contribute to inflammation [21]. Inflammatory cells such as EOS and neutrophil cells are proved to be associated with mucosa remodeling in CRS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested tissue remodeling of CRS to occur concurrently with in ammation. [20] Studies, principally in Chinese patients, have shown CRSsNP to be characterized by type 1 in ammatory patterns while CRSwNP was characterized by mixed type 2/3 in ammatory pro les. [21,22] Whether IL-19 could serve as a common downstream factor of type 1/2/3 cytokines in nasal epithelia, resulting in the regulation of MMP-9, remains unknown.…”
Section: Introductionmentioning
confidence: 99%